2021
DOI: 10.1093/ckj/sfab037
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction of COVID-19 incidence and mortality in a large multi-national hemodialysis cohort: implications for management of the pandemic in outpatient hemodialysis settings

Abstract: Background Experiences from the first wave of the 2019 coronavirus disease (COVID-19) pandemic can aide in the development of future preventive strategies. To date, risk prediction models for COVID-19-related incidence and outcomes in haemodialysis (HD) patients are missing. Methods We developed risk prediction models for COVID-19 incidence and mortality among HD patients. We studied 38 256 HD patients from a multi-national d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 43 publications
1
46
3
Order By: Relevance
“…For example, the rate of vaccination failure for hepatitis B vaccination was 28.3% of hemodialysis patients, but < 10% in the normal population [ 4 ]. Hemodialysis patients also have a higher risk of becoming infected with COVID-19 and, when infected, have a higher associated mortality rate than the normal population [ 5 , 6 ]. The immunogenicity and tolerability of SARS-CoV-2 vaccines may also differ in hemodialysis patients compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the rate of vaccination failure for hepatitis B vaccination was 28.3% of hemodialysis patients, but < 10% in the normal population [ 4 ]. Hemodialysis patients also have a higher risk of becoming infected with COVID-19 and, when infected, have a higher associated mortality rate than the normal population [ 5 , 6 ]. The immunogenicity and tolerability of SARS-CoV-2 vaccines may also differ in hemodialysis patients compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Several two-dose SARS-CoV-2 vaccines have been approved to prevent COVID-19 infection, with a reported vaccine efficacy of 90–95% in the normal population after the second dose. Dialysis patients are at high risk for COVID-19 infection and mortality [ 1 , 2 ] but were not included in the vaccination registration trials. Small observational studies showed a sufficient immune response several weeks after the second SARS-CoV-2 mRNA-based vaccination [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a 20-30% mortality rate in kidney transplant recipients hospitalized for COVID-19 [80,[128][129][130][131]. Accordingly, the French IMPORTANT study noted that the absolute number of deaths found in April 2020 was more than twofold higher than those observed in April 2018 and in April 2019 [132].…”
Section: Covid-19 In Kidney Transplant Patientsmentioning
confidence: 99%